1980
DOI: 10.1021/jm00185a016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of 5-fluoro-2'-deoxyuridine 5'-phosphorodiamidates

Abstract: Three 5'-phosphorodiamidate derivatives of 5-fluoro-2'-deoxyuridine (FdUrd), 5-fluoro-2'-deoxyuridine 5'-phosphorodiamidate (4a), 5'-phosphorodiimidazolidate (4b), and 5'-phosphorodimorpholidate (4c), were synthesized by aminolysis of 5-fluoro-2'-deoxyuridine 5'-phosphorodichloridate with the respective amine. In culture, these 5'-phosphorodiamidates inhibited the growth of murine leukemia (L5178Y) cells. 5-Fluoro-2'-deoxyuridine 5'-phosphorodiamidate (4a) was the most active derivative and, on a molar basis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…15). 109 A positive correlation was reported between the in vitro growth inhibitory potency toward L5178Y cells and the rates of hydrolysis of the phosphorodiamidates to FUdR-MP at 100 C in 0.1 M phosphate buffer (pH 7.0). The phosphorodimorphodilate of FUdR was the least potent analog (11% growth inhibition at 10 À8 M) with a half-life of 100 hr at pH 7.0 at 100 C. Phosphorodiimidazolate of FUdR had a half-life of 12 hr and exhibited only modest growth inhibition potency (16% growth inhibition at 10 À8 M).…”
Section: P H O S P H O R a M I D A T E D E R I V A T I V E S A Nucmentioning
confidence: 93%
See 3 more Smart Citations
“…15). 109 A positive correlation was reported between the in vitro growth inhibitory potency toward L5178Y cells and the rates of hydrolysis of the phosphorodiamidates to FUdR-MP at 100 C in 0.1 M phosphate buffer (pH 7.0). The phosphorodimorphodilate of FUdR was the least potent analog (11% growth inhibition at 10 À8 M) with a half-life of 100 hr at pH 7.0 at 100 C. Phosphorodiimidazolate of FUdR had a half-life of 12 hr and exhibited only modest growth inhibition potency (16% growth inhibition at 10 À8 M).…”
Section: P H O S P H O R a M I D A T E D E R I V A T I V E S A Nucmentioning
confidence: 93%
“…102, 103, 105^107 half-life of 3.9 hr). 109 Control experiments, however, found that FUdR-MP at 10 À8 M was able to inhibit 67% of the growth of L5178Y cells. Thus, the growth inhibitory activity of the phosphorodiamidates could be correlated to the rate of conversion to FUdR-MP, with decreased potency observed for compounds with the largest nitrogen-bearing substituents.…”
Section: P H O S P H O R a M I D A T E D E R I V A T I V E S A Nucmentioning
confidence: 98%
See 2 more Smart Citations
“…5'phosphordiamidate derivatives of FdUMP were synthesized and found to inhibit the growth of murine leukemia cells [5] can be cleaved to release FdUMP while the metabolic conversion of 5FU to FdUMP requires multiple enzymatic steps. [122]. The rates of activity corresponded to the rate of hydrolysis of the phosphordiamidate to FdUMP.…”
Section: Fdump Pro-drugsmentioning
confidence: 99%